KINERJA DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU DALAM MENANGANI GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU - Tobing, Ester Meilin; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Performance of Social Service and Funeral in Pekanbaru on Dealing Homeless and Beggars at Pekanbaru City. Social Department and Cemetery Pekanbaru has significance on dealing with sprawl is to conduct training which is later become input for local government programs. The importance of enforcement is process or a way to make conduciveness that aims to clean public facilities for the convenience for the public. And the importance of coaching is an action and activities undertaken for usefulness. The purpose of this study is determine the performance of the Social Department and Cemetery in Pekanbaru on managing social welfare problems in the city and to identify the factors that holding up the performance of Social Department and Cemetery in Pekanbaru on its problems. Theory (approaching system) that used as an analysis system in this research is the performance's theory and organization's theory. Based on these research, the performance of Social Department and Cemetery in Pekanbaru especially PMKS section on dealing with homeless and beggars is good enough. The effort from PMKS on handling its problems such as coaching, mental counseling, and the provision of venture capital. However the effort to round-up homeless and beggars hasn't reached the desired target. The provision of venture capital assistance is not necessarily given to each homeless and beggar in need, because the financial aid given to whoever has been selected before. The obstacles that encountered in dealing with homeless and beggars are their attitude or mindset who don't want to control, causing the PMKS's program target missed out. The other problem is lack of human resources in both the Social Department and Cemetery in Pekanbaru. Homeless and beggars mentoring process should be done so they can become self-reliant community, and in the end, the number if homeless and beggars in the Pekanbaru city can reduce as much as its can done.Keywords:Officer's Performance, Government Organization, Homeless and Beggars Development